To spray or not to spray? Understanding participation in an indoor residual spray campaign in Arequipa, Peru. Issue 1 (2nd January 2018) - Paz-Soldán, Valerie A.; Bauer, Karin M.; Hunter, Gabrielle C.; Castillo-Neyra, Ricardo; Arriola, Vanessa D.; Rivera-Lanas, Daniel; Rodriguez, Geoffrey H.; Toledo Vizcarra, Amparo M.; Mollesaca Riveros, Lina M.; Levy, Michael Z.; Buttenheim, Alison M.
ABSTRACT: Current low participation rates in vector control programmes in Arequipa, Peru complicate the control of Chagas disease. Using focus groups ( n  = 17 participants) and semi-structured interviews ( n  = 71) conducted in March and May 2013, respectively, we examined barriers to and motivators of household participation in an indoor residual spray (IRS) campaign that had taken place one year prior in Arequipa. The most common reported barriers to participation were inconvenient spray times due to work obligations, not considering the campaign to be necessary, concerns about secondary health impacts (e.g. allergic reactions to insecticides), and difficulties preparing the home for spraying (e.g. moving heavy furniture). There was also a low perception of risk for contracting Chagas disease that might affect participation. The main motivator to participate was to ensure personal health and well-being. Future IRS campaigns should incorporate more flexible hours, including weekends; provide appropriate educational messages to counter concerns about secondary health effects; incorporate peer educators to increase perceived risk to Chagas in community; obtain support from community members and leaders to build community trust and support for the campaign; and assist individuals in preparing their homes. Enhancing community trust in both the need for the campaign and its operations is key.